Fecal sludge treatment for resource recovery and biological hazard control: Phase partitioning, process intensification, and data-driven optimization - Xiaoyu Cai; Jialiang Gu; Yitian Li; Jun Nan; Defeng Xing (Chemical Engineering Journal, 2026)

Corrigendum to “Linking microbial functional partitioning with methane productivity and stability in microbial electrolysis cell–anaerobic digestion hybrid systems” [Bioresour. Technol. 453 (2026) 134629] - Xue-Ting Wang; Yanxue Li; Yuxin Pan; Xue Xing; Bo Wang; Defeng Xing; Jun Nan; Jonathan Tian En Lee; Eakalak Khan; Daniel C.W. Tsang; Nan-Qi Ren; Yong Sik Ok (Bioresource Technology, 2026)

Optimizing initial biomass to enhance microplastic sequestration via density-driven bio-flocculation in microalgal systems - Xiaoxue Mei; Jiawei Wang; Xueying Zhao; Yilu Liang; Baiyun Lu; Yawen Fan; Defeng Xing; Nanqi Ren; Yan Liu (Bioresource Technology, 2026)

Linking microbial functional partitioning with methane productivity and stability in microbial electrolysis cell–anaerobic digestion hybrid systems - Xue-Ting Wang; Yanxue Li; Yuxin Pan; Xue Xing; Bo Wang; Defeng Xing; Jun Nan; Jonathan Tian En Lee; Eakalak Khan; Daniel C.W. Tsang; Nan-Qi Ren; Yong Sik Ok (Bioresource Technology, 2026)

Effects of nanozyme on environmental fate and dissemination of antibiotic resistance genes in anaerobically digested sludge - Jing Wang; Peng Li; Ningyu Gao; Jun Ma; Defeng Xing (Bioresource Technology, 2026)

Microplastic accumulation in paired human breast tumor and para-tumor tissues and exploratory clinical associations - Limin Jia; Yanni Song; Yufeng Guo; Fuyu Yang; Qiyan Guan; Weihan Zhang; Yang Liu; Defeng Xing; Yanhong Lv (Journal of Hazardous Materials, 2026)

Synergistic hydroxyl and chlorine radicals in contact-electro-catalysis for sustainable PFAS remediation - Jin Zhang; Wei Li; Jinxing Ma; Jianghu Cui; Kuanchang He; Kui Yang; Qian Liu; Min Zhang; Sihao Lv; Faliang Cheng; Defeng Xing (Journal of Hazardous Materials, 2026)

Reutilization of digestate (residue and liquid) in the anaerobic digestion of sole corn stover: biochar preparation, methane performance and microbial responses - Haipeng Wang; Hao Sun; Sheng-Nan Zhuo; Jianrui Li; Zetang Chai; Jingwen Jia; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Journal of Environmental Management, 2026)

Electrically enhanced microalgae-bacteria systems for wastewater treatment under low-temperature conditions - Qitong Cai; Zhengpeng Wang; Xinyu Li; Yan Liu; Nanqi Ren; Defeng Xing; Xiaoxue Mei; Yawen Fan (Bioresource Technology, 2026)

Bioaugmentation of strain Bacillus sp. hex-HIT36 towards industrial wastewater 1-Hexadecene removal in biological aerated filter reactors - Lei Yang; Yijie Liu; Yuxin Pan; Xue-Ting Wang; Wei Wang; Xijun Xu; Defeng Xing; Nanqi Ren; Duu-Jong Lee; Chuan Chen (Chemical Engineering Journal, 2026)

Synergistic conversion of CH4 and CO2 into bioplastic by microalgal−bacterial consortia - Xiaowei Lv; Huihui Zhou; Yanlei Niu; Kun Feng; Nanqi Ren; Defeng Xing (Chemical Engineering Journal, 2026)

Concentration-dependent and thermal pretreatment effects of allicin on hydrogen and ethanol co-production from food waste - Jiayin Hao; Huihui Zhou; Kun Feng; Xiaoxue Mei; Nanqi Ren; Defeng Xing (Chemical Engineering Journal, 2026)

Charge-specific impacts of polystyrene nanoplastics on acidogenesis and biofilm adaptation in Ethanoligenens harbinense - Jing Wang; Weimin Zhu; Xingze Zhang; Sitong Liu; Jun Ma; Defeng Xing (Bioresource Technology, 2026)

Enhancing E. coli removal in mesophilic anaerobic digestion: New insights from inoculum comparison and metagenomic analysis - Haipeng Wang; Zetang Chai; Jianrui Li; Hao Sun; Hong-Yu Ren; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Bioresource Technology, 2025)

Self-regulating adaptability of biofilm microbiomes enhances manganese and ammonia removal in microbial electrochemical filters under dioxane exposure - Sitong Liu; Kun Feng; Dawei Zhang; Yang Liu; Jing Wang; Baiyun Lu; Defeng Xing (Journal of Hazardous Materials, 2025)

Simultaneous denitrification and phosphorus removal in MBfR with methane as the sole carbon source - Xiaowei Lv; Huihui Zhou; Jie Yang; Jiayin Hao; Zheng Zhong; Kun Feng; Defeng Xing (Journal of Environmental Management, 2025)

Energetic photoexcited electrons and enhancement of metabolic function and electron transport promote carbon chain elongation in bacterium‑cadmium sulfide biohybrid systems - Huize Fan; Jing Wang; Xiaoxue Mei; Baiyun Lu; Lei Zhao; Nanqi Ren; Defeng Xing (Chemical Engineering Journal, 2025)

Reassessing systemic blind spots in modern water disinfection paradigms - Yang Liu; Jialiang Gu; Kun Feng; Yangyang Zhang; Zheng Zhong; Sitong Liu; Defeng Xing (Journal of Hazardous Materials, 2025)

FeCN/MXene as novel heterogeneous electro-Fenton catalysts for the degradation of sulfathiazole: Performance and mechanism investigation - Huilai Liu; Zhihao Li; Defeng Kong; Xing Chen (Journal of Environmental Sciences, 2025)

AMP1-1 derived from Atractylodes macrocephala Koidz prevents bone aging triggered by lead and cadmium - Jinpeng Wang; Yu Jiang; Xiaoyu Hou; Tahir Raza; Yiping He; Xinyue Liu; Defeng Xing; Lijun Wei (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Synthetic microbiome and biochar enhanced human feces aerobic mesophilic composting - Xiaoyu Cai; Jing Wang; Kun Feng; Huihui Zhou; Chuan Chen; Chuandong Wu; Rui Fang; Defeng Xing (Resources, Conservation and Recycling, 2025)

Enhanced photocatalytic defluorination of perfluorooctanoic acid through integrated hydrogen atoms/electrons reduction and ROS oxidation with metal–organic framework heterogeneous catalysts - Cai Yan; Zheng Zhong; Jing Wang; Kun Feng; Defeng Xing (Chemical Engineering Journal, 2025)

Differentiation of the Anammox core microbiome: Unraveling the evolutionary impetus of scalable gene flow - Quan Zhang; Xiao-Ming Ji; Xueting Wang; Wei Wang; Xijun Xu; Qi Zhang; Defeng Xing; Nanqi Ren; Duu-Jong Lee; Chuan Chen (Water Research, 2025)

Applying machine learning and genetic algorithms accelerated for optimizing ethanol production - Xu Yang; Nianhua Chen; Hui Yu; Xinyue Liu; Yujie Feng; Defeng Xing; Yushi Tian (Science of The Total Environment, 2024)

Sulfur cycle-mediated biological nitrogen removal and greenhouse gas abatement processes: Micro-oxygen regulation tells the story - Yu Zhang; Wei Wang; Xijun Xu; Quan Zhang; Defeng Xing; Duu-Jong Lee; Nanqi Ren; Chuan Chen (Bioresource Technology, 2024)

Process exploration of domestication, start-up and rapid recovery strategies for anaerobic digestion of sole corn stover: Methane production efficiency and dominant microbial responses - Haipeng Wang; Hao Sun; Hong-Yu Ren; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Journal of Cleaner Production, 2024)

The generation and transformation mechanisms of reactive oxygen species in the environment and their implications for pollution control processes: A review - Zhihao Bi; Wei Wang; Lei Zhao; Xueting Wang; Defeng Xing; Yanfeng Zhou; Duu-Jong Lee; Nanqi Ren; Chuan Chen (Environmental Research, 2024)

Genome and metabolome analysis of Bacillus sp. Hex-HIT36: A newly screened functional microorganism for the degradation of 1-hexadecene in industrial wastewater - Lei Yang; Chuan Chen; Xijun Xu; Xue-Ting Wang; Defeng Xing; Nanqi Ren; Duu-Jong Lee (Environmental Research, 2024)

Enterobacter sp. HIT-SHJ4 isolated from wetland with carbon, nitrogen and sulfur co-metabolism and its implication for bioremediation - Kaili Fan; Fei Wang; Xijun Xu; Jia Shi; Wei Wang; Defeng Xing; Nanqi Ren; Duu-Jong Lee; Chuan Chen (Environmental Research, 2024)

Linking performance to dynamic migration of biofilm ecosystem reveals the role of voltage in the start-up of hybrid microbial electrolysis cell-anaerobic digestion - Xue-Ting Wang; Lei Zhao; Quan Zhang; Bo Wang; Defeng Xing; Jun Nan; Nan-Qi Ren; Duu-Jong Lee; Chuan Chen (Bioresource Technology, 2024)

Fluorocarbon polymers mediated contact-electro-catalysis activating peroxymonosulfate for emerging pollutants degradation: The key role of fluorine density in electron transfer - Dongmei Ma; Wei Li; Jin Zhang; Kuanchang He; Changyong Zhang; Gang Wang; Xiaodong Xin; Qian Liu; Faliang Cheng; Sihao Lv; Defeng Xing (Chemical Engineering Journal, 2024)

Intensified partial nitrification and microbiome response in a membrane pulsing-aerated biofilm reactor - Zheng Zhong; Kun Feng; Yu Chen; Baiyun Lu; Jing Wang; Chuandong Wu; Defeng Xing (Chemical Engineering Journal, 2024)

Application of recyclable iron-based supplementation for promoting biohydrogen and ethanol co-production - Jiayin Hao; Huihui Zhou; Jun Ma; Nanqi Ren; Defeng Xing (Fuel, 2024)

Microbiome and antibiotic resistome in bioelectrochemical toilets for onsite treatment of fecal sludge - Xiaoyu Cai; Huihui Zhou; Yu Lou; Baiyun Lu; Dawei Zhang; Jing Wang; Defeng Xing (Water Research, 2024)

Efficient removal of hexavalent chromium from wastewater using a novel sodium alginate-biochar composite adsorbent - Yushi Tian; Xiaolin Sun; Nianhua Chen; Xintong Cui; Hui Yu; Yujie Feng; Defeng Xing; Weihua He (Journal of Water Process Engineering, 2024)

Sustainable efficient utilization of magnetic porous biochar for adsorption of orange G and tetracycline: Inherent roles of adsorption and mechanisms - Jiayin Hao; Zhiliang Cui; Jiale Liang; Jun Ma; Nanqi Ren; Huihui Zhou; Defeng Xing (Environmental Research, 2024)

Overlooked in-situ sulfur disproportionation fuels dissimilatory nitrate reduction to ammonium in sulfur-based system: Novel insight of nitrogen recovery - Bo Shao; Li Niu; Yuan-Guo Xie; Ruochen Zhang; Wei Wang; Xijun Xu; Jianxing Sun; Defeng Xing; Duu-Jong Lee; Nanqi Ren; Zheng-Shuang Hua; Chuan Chen (Water Research, 2024)

Mechanisms of metabolic regulation and enhanced methane production by hydrolytic nanozyme in sludge anaerobic digestion - Jing Wang; Cai Yan; Zheng Zhong; Baiyun Lu; Chuan Chen; Lei Zhao; Jun Ma; Defeng Xing (Chemical Engineering Journal, 2024)

Linking metabolomics to machine learning reveals the metabolic fates of the refractory industrial pollutant 1-Hexadecene - Lei Yang; Xijun Xu; Jin Yan; Wei Wang; Xueting Wang; Defeng Xing; Nanqi Ren; Duu-Jong Lee; Chuan Chen (Chemical Engineering Journal, 2024)

Sequential recovery of protein and ammonium from waste sludge and functional metabolism in a combined process of nutrient recovery electro-fermentation (NREF) - Jiayu Gu; Huihui Zhou; Jing Wang; Kun Feng; Guojun Xie; Bingfeng Liu; Defeng Xing (Resources, Conservation and Recycling, 2024)

Recycling different crystal forms of MnO2 from spent Li-ion batteries cathodes for SDZ degradation - Xinxin Lv; Fang Deng; Huilai Liu; Yu Zhang; Qingjun Liu; Yueqing Liang; Defeng Kong; Mukhtar Ahmad; Xing Chen (Journal of Environmental Chemical Engineering, 2024)

Effects of polyethylene terephthalate microplastics on cell growth, intracellular products and oxidative stress of Scenedesmus sp. - Jiahui Jiang; Xiaoyu Cai; Hongyu Ren; Guangli Cao; Jia Meng; Defeng Xing; Jes Vollertsen; Bingfeng Liu (Chemosphere, 2024)

Optimization of biogas production from straw wastes by different pretreatments: Progress, challenges, and prospects - Jing Wang; Dongmei Ma; Yu Lou; Jun Ma; Defeng Xing (Science of The Total Environment, 2023)

Investigation into the treatment and resource recovery of rifamycin mycelial dreg with thermal alkaline pretreatment-anaerobic digestion - Quan Zhang; Xuejiao Gong; Yu Zhang; Xueting Wang; Xiaowen Pan; Yanfeng Zhou; Xijun Xu; Qi Zhang; Xiao-Ming Ji; Weijun Wang; Defeng Xing; Nanqi Ren; et al. (Journal of Cleaner Production, 2023)

Mechanisms of magnetic sensing and regulating extracellular electron transfer of electroactive bacteria under magnetic fields - Huihui Zhou; Xianwen Xuanyuan; Xiaowei Lv; Jing Wang; Kun Feng; Chuan Chen; Jun Ma; Defeng Xing (Science of The Total Environment, 2023)

Carbon-based materials as highly efficient catalysts for the hydrogen evolution reaction in microbial electrolysis cells: Mechanisms, methods, and perspectives - Lina Xu; Wei Li; Jiaqin Luo; Lingyu Chen; Kuanchang He; Dongmei Ma; Sihao Lv; Defeng Xing (Chemical Engineering Journal, 2023)

Co-treatment with free nitrous acid and calcium peroxide regulates microbiome and metabolic functions of acidogenesis and methanogenesis in sludge anaerobic digestion - Jing Wang; Yu Lou; Dongmei Ma; Kun Feng; Chuan Chen; Lei Zhao; Defeng Xing (Science of The Total Environment, 2023)

Conductive carrier promotes synchronous biofilm formation and granulation of anammox bacteria - Kun Feng; Yu Lou; Yitian Li; Baiyun Lu; Anran Fang; Guojun Xie; Chuan Chen; Defeng Xing (Journal of Hazardous Materials, 2023)

Formation of PCDD/Fs, PCBs and HCl during catalytic combustion of chlorobenzene over supported transition metal (Cr, V and Cu) oxide catalysts - Defeng Xing; Sheng Wang; Yun Fan; Haijun Zhang; Ting Wang; Mingzhe Wang; Shudong Wang; Jiancheng Wang; Dahai Pan; Xueding Song (Journal of Environmental Chemical Engineering, 2023)

Biochar prepared from human feces (HFBC) as a promoter in biohydrogen production using simulated feces as substrate - Pian-Pian Xu; Kai Sun; Jian Du; Guojun Xie; Defeng Xing; Bing-Feng Liu (Chemical Engineering Journal, 2023)

Metagenomic reveals the methanogenesis metabolic mechanism of high-solids anaerobic digestion of human feces under gradient domestication - Haipeng Wang; Hao Sun; Hongyu Ren; Guangli Cao; Guojun Xie; Defeng Xing; Nanqi Ren; Bingfeng Liu (Chemical Engineering Journal, 2023)

Thermophilic dark fermentation fast start-up of hydrogen production with substrate concentration regulation and moderate pretreatment inoculum - Tianming Yin; Wei Wang; Shengnan Zhuo; Guangli Cao; Hongyu Ren; Jianrui Li; Defeng Xing; Guojun Xie; Bingfeng Liu (Fuel, 2023)

Effects of sludge lysate for Cr(VI) bioreduction and analysis of bioaugmentation mechanism of sludge humic acid - Hongling Chen; Ruofei Jin; Guangfei Liu; Tian Tian; Chen Gu; Jiti Zhou; Defeng Xing (Environmental Science and Pollution Research, 2019)

Controllable synthesis Fe3O4@POHABA core-shell nanostructure as high-performance recyclable bifunctional magnetic antimicrobial agent - Zhijia Zhang; Defeng Xing; Xin Zhao; Xiaojun Han (Environmental Science and Pollution Research, 2017)

Microbial community structure of ethanol type fermentation in bio‐hydrogen production - Nanqi Ren; Defeng Xing; Bruce E. Rittmann; Lihua Zhao; Tianhui Xie; Xin Zhao (Environmental Microbiology, 2007)
Summary Three continuous stirred‐tank reactors (CSTRs) were used for H 2 production from molasses wastewater at influent pH of 6.0–6.5 (reactor A), 5.5–6.0 (reactor B), or 4.0–4.5 (reactor C). After operation for 28 days, the microbial community formed ethanol type (C), propionate type (A) and ethanol‐butyrate‐mixed type (B) fermentation. The H 2 production rate was the highest for ethanol type fermentation, 0.40 l (g VSS) −1 day −1 or 0.45 l H 2 (g COD removed) −1 . Microbial community dynamics and diversity were analysed using double‐gradient denaturing gradient gel electrophoresis (DG‐DGGE). Denaturing gradient gel electrophoresis profiles indicated that the community structures changed quickly in the first 14 days. Phylogenetic analysis indicated that the dominant bacterial groups were low G+C Gram‐positive bacteria, Bacteroides , γ‐Proteobacteria and Actinobacteria ; α‐Proteobacteria , β‐Proteobacteria , δ‐Proteobacteria and Spirochaetes were also presented as minor groups in the three reactors. H 2 ‐producing bacteria were affiliated with Ethanoligenens , Acetanaerobacterium , Clostridium , Megasphaera , Citrobacter and Bacteroides. An ethanol‐based H 2 ‐producing bacterium, Ethanoligenens harbinense CGMCC1152, was isolated from reactor C and visualized using fluorescence in situ hybridization (FISH) to be 19% of the eubacteria in reactor C. In addition, isoenzyme activity staining for alcohol dehydrogenase (ADH) supported that the majority of ethanol‐producing bacteria were affiliated with Ethanoligenens in the microbial community.